Marin Barletiâ€™s Masterpiece, The Siege of Shkodra: A Historical Review - Hosaflook, David (Mediterranean Journal of Social Sciences, 2012)
â€œThe Siege of Shkodraâ€ is regarded by Albanians as the first work of Albanian history by the first known Albanian author.The book was written in Latin in 1504 and was finally translated into English in 2012. The work describes the 1478â€“9 Ottoman siege ofShkodra, described by Franz Babinger as â€œone of the most remarkable episodes in the struggle between the West and the Crescentâ€(363). The work is organized into three large chapters called â€œbooksâ€: Book One is introductory with attention to the situationalbackground and the origins of the Turks; Book Two describes the massive Turkish attack and the heroic Albanian and Venetian defense;Book Three describes the sultan halting the attack, conquering smaller nearby citadels, and returning to Istanbul, where he soon wouldsign an accord with Venice, which ceded Shkodra to him as a prerequisite for peace.